2020
DOI: 10.1007/s11356-020-09433-5
|View full text |Cite
|
Sign up to set email alerts
|

Defect minimized Ag-ZnO microneedles for photocatalysis

Abstract: A facile solution processing strategy has been developed for the formation of Ag-modified ZnO microneedles at various calcination temperatures such as 300, 500, and 700 °C (AZ3, AZ5, and AZ7 respectively). Due to the heavy doping of AgNO 3 , Ag + ions have been incorporated in to the crystal lattice of ZnO in all the Ag-ZnO samples, which facilitated the formation of Ag-ZnO microneedle morphology with minimized defect states, and obviously, the plasmon peaks were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…By contrasting and comparing our DLTS results with the reported defect levels [43,47,55,62,65,67,74], the authors conclude that the origins of all the synthesized ZnO nanostructure's P 1 , P 2 , P 3 , P 4 , and P 5 defects are Zinc antisites (Zn o ), Zinc vacancies (V zn ), Zinc interstitials (Zn i ), Oxygen vacancies (V o ), and Oxygen interstitials (O i ), respectively. However, we did not identify any defect energy levels related to Oxygen antisites (O zn ).…”
Section: Dlts Analysismentioning
confidence: 75%
See 2 more Smart Citations
“…By contrasting and comparing our DLTS results with the reported defect levels [43,47,55,62,65,67,74], the authors conclude that the origins of all the synthesized ZnO nanostructure's P 1 , P 2 , P 3 , P 4 , and P 5 defects are Zinc antisites (Zn o ), Zinc vacancies (V zn ), Zinc interstitials (Zn i ), Oxygen vacancies (V o ), and Oxygen interstitials (O i ), respectively. However, we did not identify any defect energy levels related to Oxygen antisites (O zn ).…”
Section: Dlts Analysismentioning
confidence: 75%
“…However, researchers also have claimed that defect energies between 0.5 eV and 0.9 eV below the conduction energy band occur due to Oxygen vacancies (V o ) in ZnO crystalline samples [65][66][67][68][69]. Chai et al found a deep donor at 0.83 eV, which occurs due to Oxygen vacancies (V o ) [68].…”
Section: Dlts Analysismentioning
confidence: 99%
See 1 more Smart Citation